Synthesis of Cuprous Oxide (Cu2O) Nanoparticles – a Review - Sachin S. Sawant; Ashok D. Bhagwat; Chandrashekhar M. Mahajan (Журнал нано- та електронної фізики)
Cuprous Oxide (Cu2O) a semiconductor material oxide; with unique optoelectronic properties; gains significant importance for its synthesis in view of its various technological and industrial applications. A few liquid phase methods for the synthesis of Cu2O nanoparticles are reviewed on the basis of materials, methodology, synthesis conditions and key findings. A comparative study of these methods is also performed following criteria of repeatability, safety, cost, time span and simplicity. Contextual to the above mentioned criteria, three liquid phase synthesis techniques were shortlisted and actually experimented (as reported) to synthesize the Cu2O nanoparticles. This was done to investigate the effectiveness, repeatability and stability of the synthesized Cu2O product as a function of ageing time. The synthesized Cu2O using all these techniques are prone to be unstable and undergo the rapid phase change to CuO phase which was ascertained from the shift of absorbance peak in UV-VIS spectra. The results have highlighted the urgent need to develop a facile, economical, scalable and safe method to synthesize stable Cu2O nanoparticles at room temperature.